Avaliação da estratégia multimodal de melhoria da higienização das mãos da Organização Mundial de Saúde em um hospital universitário brasileiro - Pereira, Eliana Borges Silva (2015)
Healthcare-associated infections (HAIs) represent a great risk factor to patient well-being, which in turn brings a significant economic factor onto health services worldwide. Hand hygiene (HH) is considered a high impact measure with the least expense incurred when it comes to controlling infections related to health care, as it avoids the cross transmission of microorganisms. This study aimed to evaluate the effectiveness of the multimodal strategy to improve the HH from the World Health Organization (WHO) in a Brazilian University hospital. This is an ecological study, prospective, pre and post-intervention type, conducted between December 2012 and October 2013. Data were collected by direct observation and employment self-administered instrument to health professionals from seven inpatient units: Adult Intensive Care Unit (AICU), Pediatric Intensive Care Unit (PICU), Kidney Transplant Sector (SECTRAN), Internal Medicine (IM), Clinical Surgery 1 (SC1), Clinical Surgery 2 (SC2), Burn Unit (BU). HAI rates were evaluated, joining the HM and the knowledge and perception of health professionals in relation to IRAS and HM. There were 2.297 hand hygiene opportunities observed. The adherence rate was of 54.86% during the pre-intervention period and 51.02% for post-intervention (p>0.05). The authors did not find any direct relationship between the rates of adherence of hand hygiene with infections related to health care. One of the failures detected in the implementation design, was the fact that feedback of infection rates related to health care did not include that of health care professionals. It is concluded that the implementation of the multimodal strategy to improve the HM the WHO is not necessarily effective.